PENGEMBANGAN MODUL PEKERJAAN DASAR TEKNIK MESIN BERBASIS PROJECT BASED LEARNING DI JURUSAN TEKNIK PEMESINAN SMK NEGERI 5 PADANG - Winaldi Alfonis; Nofri Helmi Helmi; Refdinal Refdinal; Arwizet K (Unversitas Negeri Padang, 2020)
Limited learning media can lead to the lack of competence of students in learning. The purpose of this research is to produce a basic learning module of mechanical engineering based on Project Based Learning that is valid, practical and feasible for use in the mechanical engineering department of SMK Negeri 5 Padang. The Project Based Learning model provides students with opportunities to improve problem solving skills and improve knowledge, skills, attitudes and productivity competencies. The development methods used in this study are the 4-D (Four D-Model) development method consisting of the four main phases in Define, Design, Develop and Disseminate. This research data was obtained from the validation of 1 lecturer and 1 lecturer in media experts and practical data obtained from respondents 1 Teacher and 30 students. Based on the results of this development study obtained a percentage of validation results by material experts get a value of 86.75% including into a very valid category and validation results by media experts to achieve a value of 85.00% including into a very valid category. Practicality results of teacher response learning module get a percentage score of 96.25% including into a very practical category and the response results of students get a score of 95.75% included in the very practical category. Based on the validation and practicality results can be concluded that this learning module deserves to be used as a learning medium.. Keywords : Development, Modules, Project Based Learning, Methods